supG and supL in Escherichia coli code for mutant lysine tRNAs+. - Prather, N E (1983)
We have determined the nucleotide sequences of lysine tRNAs isolated from strains containing one or the other of two Escherichia coli ochre suppressors, supG and supL. Each strain, besides producing wild-type lysine tRNA, has a mutant lysine tRNA species that apparently can read the polypeptide chain termination codons UAA and UAG. The mutant tRNAs from supG and supL strains are identical. In each case the suppressor tRNA has an A36 for U36 nucleotide substitution. Furthermore, the hypermodified nucleoside at position 37 has been changed from t6A to ms2i6A.